Multifunctional hollow sandwich structure with many active sites for electronic transfer modulation and its application in energy storage and conversion. Issue 5 (12th June 2019) - Wang, Wen; Yao, Jixin; Zuo, Xueqin; Yang, Qun; Wu, Mingzai; Tang, Huaibao; Jin, Shaowei; Li, Guang
Abstract : Revealing the fundamental mechanism of effective, low-cost multifunctional electrocatalysts based on a hollow sandwich structure is desirable for energy storage and conversion. Abstract : Revealing the fundamental mechanism of effective, low-cost multifunctional electrocatalysts based on a hollow sandwich structure is desirable for energy storage and conversion. Transition metal sulfides (TMS) and carbon-based heteroatom-doped materials are designed to achieve hollow structures with large specific surface areas. These materials require the well-organized integration of dual carbon layers with different morphologies and active Ni3 S2 nanosheets to form a multifunctional electrocatalyst. The interactions among the three components also require elucidation. In this work, we synthesized N-doped hollow carbon spheres (NHC) to obtain a large specific surface area and many active sites. Then, hierarchical Ni3 S2 nanosheets were adhered to the NHC surfaces to form an NHC/Ni3 S2 nanocomposite. The nanocomposite was encapsulated in reduced graphene oxide (RGO) to form an NHC/Ni3 S2 /RGO sandwich structure. The NHC/Ni3 S2 /RGO nanocomposite showed outstanding performance as a multifunctional catalyst in dye-sensitized solar cells (DSSCs), in the acidic hydrogen evolution reaction (HER), and in the energy storage systems of supercapacitors (pseudocapacitance). A DSSC containing the nanocomposite as a counter electrode achieved a photoelectric conversion efficiency (PCE) of up to 9.03%. The specific capacitance of the supercapacitor containing the nanocomposite was 990.6 F g −1 . When the composite was used as a catalytic electrode for the HER, a current density of 10 mA cm −2 was achieved with an overpotential of only −142 mV. In addition, the Tafel slope (98.1 mV dec −1 ) in 0.5 M H2 SO4 solution was small. This work contributes a strategy for the development of multifunctional catalytic materials for energy storage and conversion.